Business incubators as vectors to the promotion of clean technologies in small firms: Limits and possibilities - Fonseca, Sergio Azevedo [UNESP] (FapUNIFESP (SciELO), 2015)
This paper reports the results of a study that sought to reflect, based on two cases, upon opportunities and challenges, possibilities and limits, for the insertion of small business ventures - new ventures and micro and small enterprises - in the productive field that became known, especially after the Rio Conference 92, as green economy. The search for clean technologies has become a great challenge and at the same time, a great business opportunity. The possibilities were opened up for large companies, able to mobilize the necessary resources for this transition. The limits were evident for small businesses. Evidence has been pointing out the necessity of developing instruments, particularly on public policies, able to offer support to small businesses so that they can overcome their limits. The focus of the study was precisely on this point: the experience of two incubators, one American and another Brazilian, specialized in supporting small businesses oriented to the markets of clean technologies. Qualitative in the method and with exploratory purposes, the research was designed as a multiple case study (based on two cases), having the documentary research as strategy for data collection. Supported by the literature of environmental management (with emphasis on small businesses with clean technologies) and business incubators (with greater emphasis on the typology of incubators), the research revealed a large gap between the realities of the two countries, either in numbers of incubators within the field of clean technologies, or in the mobilization of institutional actors who act in support of these incubators. Based on the two case studies it was possible to identify a single strategic affinity between the two incubators and a set of dichotomous elements, both strategically and in terms of management. In view of these findings, as conclusions of the paper, some suggestions are pointed out for the Brazilian movement of incubators in the will to incorporate environmental elements into their strategies and their management systems.
Incubadoras como vetores para a promoção de tecnologias limpas em empreendimentos de pequeno porte: Possibilidades e limites
Keywords: Business incubators; Clean technologies; Clean technology incubators; Environmental management; Micro and small firms